Handbook on Project Management and Scheduling Vol.1 - Schwindt, Christoph (Springer, 2015)
Due to the increasing importance of product differentiation and collapsing product life cycles, a growing number of value-adding activities in the industry and service sector are organized in projects. Projects come in many forms, often taking considerable time and consuming a large amount of resources. The management and scheduling of projects represents a challenging task, and project performance may have a considerable impact on an organization's competitiveness.